Analisis Faktor - Faktor Yang Mempengaruhi Komplain Nasabah Terhadap Klaim Asuransi Jasindo Kantor Cabang Kupang - Emba, Yohanes P. R.; Kellen, Pius Bumi; Ballo, Fransina W. (Politeknik Negeri Ambon, 2024)
This research reviews customer experiences regarding the claims process at insurance companies, with a focus on expiry of contract claims, cash value claims and maintenance cost claims. The findings show that customers generally complain about the slow claim process, which significantly influences negative perceptions of the company's services. While customers appreciate good communication and transparency in claims procedures, there is still a need to increase clarity regarding claims terms and conditions. Customers also highlighted the desire for simplification in the collection of required documents, considering complicated processes as a major obstacle that needs to be overcome. The company's responsiveness to questions and complaints is considered quite good, but there is hope to improve the speed of response, especially in handling claims. These findings indicate the need for insurance companies to focus on improving the efficiency of the claims process and more effective communication to increase customer satisfaction and improve the company's reputation. In the competitive context of the insurance industry, effective management of the claims process is crucial to maintaining customer satisfaction and maintaining their loyalty. This research shows that customers not only want a fast and efficient claims process but also expect transparency and convenience at every stage of the claim. Insurance companies can utilize these findings to identify areas that require improvement, such as simplifying the claims process and increasing the accessibility of information regarding claim requirements. Keywords: claims process, customer satisfaction, transparency, ease of proce